PERTUMBUHAN DAN HASIL BAYAM YANG DIBERI POC LIMBAH CAIR TAHU DAN DAUN GAMAL DENGAN LAMA FERMENTASI BERBEDA - Nova Deviyanti Lussy; Chatlimbi T. Br. Panjaitan; Chris N. Namah (Politeknik Pertanian Negeri Kupang, 2022)
Application of LOFs with different fermentation duration determined the LOFs quality and expected to affect the growth and yield of plants. This study aimed to determine the effect of LOF (tofu liquid waste and Gamal leaves) fermentation duration on the growth and yield of spinach. This research used a Randomized Block Design with 6 fermentation duration treatments (5; 10; 15; 20; 25; and 30 days) and 4 replications. The data were analyzed for variance and would be continued with the 5% BNJ test if there was a significant effect. The results showed that the best LOFs fermentation duration was 20 days was. it was shown the highest spinach plants 16.75 cm at 14 days after planting (DAP) and 55.38 cm at 23 DAP; the highest number of leaves was 28.88 at 14 DAP and 70.13 at 23 DAP; plant fresh weight 296.65 g; the dry weight 30.31 g. Keywords: Liquid Organic Fertilizer, tofu waste, gamal, spinach, fermentation time